Discovery of bioactive peptides as therapeutic agents for skin wound repair - Md Fadilah, Nur Izzah; Shahabudin, Nurul Aqilah; Mohd Razif, Raniya Adiba; Sanyal, Arka; Ghosh, Anushikha; Baharin, Khairul Idzwan; Ahmad, Haslina; Maarof, Manira; Motta, Antonella; Fauzi, Mh Busra (SAGE Publications Ltd, 2024)
Short sequences of amino acids called peptides have a wide range of biological functions and the potential to treat a number of diseases. Bioactive peptides can be derived from different sources, including marine organisms, and synthetic design, making them versatile candidates for production of therapeutic agents. Their therapeutic effects span across areas such as antimicrobial activity, cells proliferation and migration, synthesis of collagen, and more. This current review explores the fascinating realm of bioactive peptides as promising therapeutic agents for skin wound healing. This review focuses on the multifaceted biological effects of specific peptides, shedding light on their potential to revolutionize the field of dermatology and regenerative medicine. It delves into how these peptides stimulate collagen synthesis, inhibit inflammation, and accelerate tissue regeneration, ultimately contributing to the effective repair of skin wounds. The findings underscore the significant role several types of bioactive peptides can play in enhancing wound healing processes and offer promising insights for improving the quality of life for individuals with skin injuries and dermatological conditions. The versatility of peptides allows for the development of tailored treatments catering to specific wound types and patient needs. As continuing to delve deeper into the realm of bioactive peptides, there is immense potential for further exploration and innovation. Future endeavors may involve the optimization of peptide formulations, elucidation of underlying molecular and cellular mechanisms.